Bika ( Cocoa Beans) Into Processed Chocolate - Eti Meirina Brahmana; Dahlia; Jismi Mubarrak; Dina Rosita; Miftahul Jannah (Universitas Lancang Kuning, 2023)
SMK Zaidar Yahya located in Rokan Hulu Regency had a food service department that had one of the expertise competencies, namely entrepreneurs in the field of food supply business. These students had a golden opportunity in the processing of chocolate from cocoa beans (Theobromo cacao, L.). The methods used were site surveys and discussions with partners, trials of chocolate making in the laboratory, training and socialization, and evaluation. The results of the service showed an increase in partner empowerment where partners understood 77.27% of the material delivered based on the pretest and posttest results provided. Increased knowledge of economic value from upstream to downstream. Increased motivation to become an entrepreneur and willingness to learn and try optimally. The availability of simple cocoa bean processing facilities and increased knowledge of partners in processing cocoa beans. Increased knowledge about the technology of processing cocoa beans into processed chocolate such as milk chocolate and dark chocolate. Analysis of the satisfaction survey showed that the category was very satisfied with a value of 91.04%.